2013
DOI: 10.1074/jbc.m113.472373
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated Receptor 1 (PAR1) and PAR4 Heterodimers Are Required for PAR1-enhanced Cleavage of PAR4 by α-Thrombin

Abstract: Background: Protease-activated receptor 1 (PAR1) and PAR4 mediate thrombin signaling in platelets. Results: Mutations in transmembrane helix 4 (TM4) of PAR1 or PAR4 disrupts ␣-thrombin-induced heterodimerization and PAR1-assisted PAR4 cleavage. Conclusion: PAR1-PAR4 heterodimers are required for efficient PAR4 cleavage. Significance: The dimerization of PAR1 and PAR4 may impact the effectiveness of PAR1 antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
72
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 49 publications
(78 reference statements)
5
72
0
1
Order By: Relevance
“…22,23 In each case, the enhanced rate of PAR4 cleavage by thrombin is dependent on PAR4 heterodimerization. 23,78,79 In platelets, PAR4 also forms agonist dependent heterodimers with the ADP receptor, P2Y12. 76,77 Li et al showed that simultaneous stimulation of PAR4 and P2Y12 resulted in arrestin-2 recruitment to PAR4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 In each case, the enhanced rate of PAR4 cleavage by thrombin is dependent on PAR4 heterodimerization. 23,78,79 In platelets, PAR4 also forms agonist dependent heterodimers with the ADP receptor, P2Y12. 76,77 Li et al showed that simultaneous stimulation of PAR4 and P2Y12 resulted in arrestin-2 recruitment to PAR4.…”
mentioning
confidence: 99%
“…PARs are no exception as evidence exists for both constitutive and agonist-induced dimers. 8,23,[75][76][77][78] The major point of contention regarding the organization of GPCRs is defining a reliable readout for oligomerization of receptors in native tissues. PARs have a distinct advantage over other receptor families because they cooperate in specific ways that are consistent with dimerization or oligomerization.…”
mentioning
confidence: 99%
“…75 Additionally, affinity tag removal from the N-terminal domain of Platelet Activating Factor proteins have facilitated heterodimer formation. 76 Without the his-tag, the Δ85 IncA dimer is 42.6 kDa, and the elution pattern was consistent with expectations ( Figure 4.4). 74 SEC data presented here suggest specificity in structural alignment exists to promote dimer formation and the monomer population is produced by interference by the flexible his-tag.…”
supporting
confidence: 74%
“…25,28 Although there may have been a small reduction in total receptor expression in this overexpression model, we showed that the Y157C substitution resulted in much more marked reduction of surface expression of PAR4, thereby reducing the availability of receptor to respond extracellular agonists. Consistent with this, PAR4 Y157C showed greater colocalization than PAR4 WT with the ER exit-marker calnexin, but less colocalization with early endosome antigen 1, which is a marker of endosomes that mediate GPCR internalization after surface membrane expression.…”
Section: Discussionmentioning
confidence: 93%
“…2 The preservation of PAR1-AP responses in the PAR4 Y157C platelets is less consistent with previous observations in transfected cell models that PAR1-PAR4 heterodimer formation is necessary for full PAR1 expression and function. 28 It is not possible to resolve from these functional data whether the heterozygous Y157C substitution in the cases disrupts PAR4 homodimer formation, 29 which could contribute to the loss of PAR4 responsiveness phenotype.…”
Section: Discussionmentioning
confidence: 99%